In vitro myotrophic effect of serum kappa chain immunoglobulins from a patient with kappa light chain myeloma and muscular hypertrophy. - Delaporte, C (1986)
Muscle hypertrophy due to enlarged muscle fibers was accompanied by kappa light chain myeloma in a 62-yr-old man. Immunofluorescence showed kappa light chain deposits around muscle fibers. We hypothesized that a circulating growth factor may be involved in the pathogeny of this muscular hypertrophy. Patient serum cultured with muscle cells showed that (a) the patient's serum exhibited a trophic effect on human muscle cells in culture, (b) this trophic effect increased the differentiation and did not influence the proliferation of human muscle cells, and (c) the fraction of the patient's serum immunoadsorbed on antihuman kappa chain antibodies exhibited the same in vitro effect on the muscle cells, whereas the fraction immunoadsorbed on antihuman lambda chain antibodies did not. These results support the hypothesis that the patient's kappa light chains have a specific enhancing effect on human muscle cell differentiation, perhaps leading to an acquired muscular hypertrophy.